(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
This is an experience report whose aim is to describe the deployment process, development, and challenges of the Observatory of Mental Health and Policies on Drugs. The observatory was idealized in 2020, which main aim was to collect and compile institutional research, thesis, dissertations, monographs, articles, books, book chapters, and technical productions, intending to promote the devolution of theses productions to society. Thus, the observatory users can conduct research and share their work in social media. Nowadays, there is a collection of 140 works. Challenges are mainly related to the valorization of this tool as a means of research and publicity of the observatory, which grows gradually. Nevertheless, we conclude that the Observatory of Mental Health and Policies on Drugs has social relevance for researchers and the population in general, by providing democratization of scientific knowledge in the mental health field.